2008
DOI: 10.1080/02640410701352018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in jump performance and muscle activity following soccer-specific exercise

Abstract: The jump performance of ten youth soccer players (mean age 15.8 years, s= 0.4) was assessed before and after 42 min of soccer-specific exercise performed on a non-motorized treadmill. A squat, countermovement, and drop jump were performed on a force platform and simultaneously surface EMG activity of four lower limb muscles was collected. Jump height deteriorated across all conditions with mean reductions of - 1.4 cm (s = 1.6; P < 0.05), - 3.0 cm (s = 2.9; P < 0.05), and -2.3 cm (s = 1.7; P < 0.01) in the squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
5
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 19 publications
11
78
5
6
Order By: Relevance
“…The test has previously been shown to be valid and reliable when assessing youth male soccer players (Oliver et al 2007) and has previously been employed to identify decrements in jump performance in a youth population (Oliver et al 2008). During the test players cover approximately 5 km, with mean physiological load previously reported to be 70  3 % of 2 O V  max (Oliver et al 2007).…”
Section: Soccer-specific Intermittent Exercise Test (Ssiet)mentioning
confidence: 99%
See 2 more Smart Citations
“…The test has previously been shown to be valid and reliable when assessing youth male soccer players (Oliver et al 2007) and has previously been employed to identify decrements in jump performance in a youth population (Oliver et al 2008). During the test players cover approximately 5 km, with mean physiological load previously reported to be 70  3 % of 2 O V  max (Oliver et al 2007).…”
Section: Soccer-specific Intermittent Exercise Test (Ssiet)mentioning
confidence: 99%
“…Exercise was organised into repetitive 2 min periods of activity as follows; 45 s walking (4 km.h -1 ), 15 s cruising (12 km.h -1 ), 15 s stationary, 40 s jogging (8 km.h -1 ) and a 5 s maximal sprint. The SSIET was performed on a Woodway Tramp non-motorised treadmill (Woodway GmbH, Germany) as per procedures described elsewhere (Oliver et al 2007;Oliver et al 2008). A visual display monitor placed in front of the treadmill allowed participants to monitor their velocity, with verbal feedback given by the instructor whenever a change in velocity was necessary.…”
Section: Soccer-specific Intermittent Exercise Test (Ssiet)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it has been observed that a previous long-term endurance exercise can adversely influence both strength and power (Chambers, Noakes, Lambert, & Lambert, 1998;Lepers, Pousson, Maffiuletti, Martin, & Van Hoecke, 2000;Millet et al, 2002;Nicol, Komi, & Marconnet, 1991). Other researchers have reported a decrease in jumping and kicking performance under fatiguing conditions (Abt, Reaburn, Holmes, & Gear, 2003;Hoffman, Nusse, & Kang, 2003;Kellis, Katis, & Vrabas, 2006;Lees & Davies, 1988;Oliver, Armstrong, & Williams, 2006;Perroni et al, 2006). In these studies, jumping or kicking performance was measured after a soccer match, an exercise protocol that simulated a soccer match or a muscular endurance exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The CMJ test was carried out according to previously described methods 11 using a portable photoelectric cell system (Optojump, Microgate, Bolzano, Italy). This equipment is both reliable and valid for vertical jump assessment 12,13 .…”
Section: Countermovement Jump Performancementioning
confidence: 99%